Chandra spatially resolved spectroscopic study and multiwavelength imaging of the supernova remnant 3C 397 (G41.1-0.3) - Safi Harb, S. (2005)
We present a Chandra observation of the supernova remnant (SNR) 3C 397 (G41.1 0.3) obtained with the Advanced CCD Imaging Spectrometer (ACIS-S). Previous studies of this SNR have shown that the remnant harbors a central X-ray ‘‘hot spot’’ suggestive of a compact object associated with 3C 397. With the Chandra data, we can rule out the nature of the hot spot as a pulsar or a pulsar wind nebula and put an upper limit on the flux of a hidden compact object of FX(0:5 10 keV ) 6 ; 10 13 ergs cm 2 s 1. We found two point sources in the observed Chandra field. We argue that neither of them is associated with 3C 397 and that the hard source, CXO J190741.2+070650, which is characterized by a heavily absorbed spectrum with a strong Fe line, is a newly discovered active galactic nucleus. The Chandra image reveals arcsecond-scale clumps and knots that are strongly correlated with the radio VLA image, except for the X-ray hot spot. Our Chandra spatially resolved spectroscopic study shows that one-component models are inadequate and that at least two nonequilibrium ionization thermal components are needed to fit the spectra of each selected region. The derived average spectral parameters are consistent with the previous global ASCA fits performed by Safi-Harb and coworkers. However, the hard component requires a high abundance of Fe indicating the presence of hot Fe ejecta. When comparing the eastern with the western lobe, we find that the column density, the brightness, and the ionization timescales are generally higher for the western side. This result, combined with our study of the 3C 397 environs at millimeter wavelengths, indicates a denser medium to the west of the SNR. Our multiwavelength imaging and spectral study favors the scenario in which 3C 397 is a 5300 year old SNR expanding in a medium with a marked density gradient and is likely to be encountering a molecular cloud on the western side. We propose that 3C 397 will evolve into a mixed-morphology SNR.